Proton Radiation Hardness of Organic Photovoltaics: An In‐Depth Study. Issue 6 (1st March 2022) - Lee, Harrison Ka Hin; Stewart, Katherine; Hughes, Declan; Barbé, Jérémy; Pockett, Adam; Kilbride, Rachel C.; Heasman, Keith C.; Wei, Zhengfei; Watson, Trystan M.; Carnie, Matthew J.; Kim, Ji-Seon; Tsoi, Wing Chung
Abstract : Recent developments of solution‐processed bulk‐heterojunction organic photovoltaic (OPV) cells have demonstrated power conversion efficiencies (PCEs) as high as 18% for single‐junction devices. Such a high PCE in addition to its desirable lightweight property and high mechanical flexibility can realize high specific power and small stowed volume, which are key considerations when choosing PV for space missions. To take one important step forward, their resilience to ionizing radiation should be well studied. Herein, the effect of proton irradiation at various fluences on the performance of benchmark OPV cells is explored under AM0 illumination. The remaining device performance is found to decrease with increasing proton fluence, which correlates to changes in electrical and chemical properties of the active layer. By redissolving the devices, the solubility of the active layer is found to decrease with increasing proton fluence, suggesting that the active materials are likely cross‐linked. Additionally, Raman studies reveal conformational changes of the polymer leading to a higher degree of energetic disorder. Despite a drop in performance, the retaining percentage of the performance is indeed higher than the current market‐dominating space PV technology—III–V semiconductor‐based PV, demonstrating a high potential of the OPV cell as a candidate for space applications. Abstract : High energy proton irradiation causes organic photovoltaic (OPV) cells degradation. The solubility of the active layer PTB7‐Th:PC71 BM is substantially reduced, suggesting cross‐linking can happen due to the irradiation. Raman spectroscopy reveals conformational changes on the PTB7‐Th at high proton fluence. Interestingly, despite a drop in performance, the percentage drop is in fact lower than for III–V semiconductor‐based PV.